Integration of Electronic Medical Record and SATUSEHAT’s Platform : Patient’s Legal Protection Perspective - Budiyanti, Rani Tiyas; Herlambang, Penggalih Mahardika; Fuad, Anis; Kusumastuti, Wulan (Health Science UDINUS, 2023)
SATUSEHAT’s platform has been implemented as a form of digital transformation in health services in Indonesia. This platform includes features that facilitate data integration from medical records, medical resumes, and various similar health platforms with the concept of interoperability and data sharing between healthcare facilities in Indonesia. Data sharing and ownership of patient data raises various ethical and legal issues in its application, especially when it relates to the right to patient data in electronic medical records (EMR) in health services. However, in the guidelines for the implementation of EMR, there is no general consent regarding the release of the data. This study aims to analyze legal issues that can occur and recommendations related to the implementation of SATUSEHAT which is integrated with EMR of health care facilities and to develop legal concepts in its application. The method used uses a statutory approach and conceptual. General consent regarding the release of EMR data to be integrated with SATUSEHAT needs to be applied. Several issues may arise regarding the implications of refusing or approving the integration of EMR with SATUSEHAT such as security, confidentiality, and data usage. Healthcare facilities should include general consent regarding the integration of the data as a separate option in the clause in the general consent which is preceded by information regarding the risks and benefits obtained. Guarantees regarding the security and privacy of patient data by both health facilities and the SATUSEHAT’s platform also need to be strengthened so that they do not harm patients. In addition, guidelines regarding data access and ownership need to be developed, and clarification on the responsible party and the sanctions to be imposed in the event of a data leakage need to be further defined